Rhamnolipid the Glycolipid Biosurfactant: Emerging trends and promising strategies in the field of biotechnology and biomedicine - Thakur, Priyanka; Saini, Neeraj K.; Thakur, Vijay Kumar; Gupta, Vijai Kumar; Saini, Reena V.; Saini, Adesh K. (Microbial cell factories, 2021)
Rhamnolipids (RLs) are surface-active compounds and belong to the class of glycolipid biosurfactants, mainly produced from Pseudomonas aeruginosa . Due to their non-toxicity, high biodegradability, low surface tension and minimum inhibitory concentration values, they have gained attention in various sectors like food, healthcare, pharmaceutical and petrochemicals. The ecofriendly biological properties of rhamnolipids make them potent materials to be used in therapeutic applications. RLs are also known to induce apoptosis and thus, able to inhibit proliferation of cancer cells. RLs can also act as immunomodulators to regulate the humoral and cellular immune systems. Regarding their antimicrobial property, they lower the surface hydrophobicity, destruct the cytoplasmic membrane and lower the critical micelle concentration to kill the bacterial cells either alone or in combination with nisin possibly due to their role in modulating outer membrane protein. RLs are also involved in the synthesis of nanoparticles for in vivo drug delivery. In relation to economic benefits, the post-harvest decay of food can be decreased by RLs because they prevent the mycelium growth, spore germination of fungi and inhibit the emergence of biofilm formation on food. The present review focuses on the potential uses of RLs in cosmetic, pharmaceutical, food and health-care industries as the potent therapeutic agents.